Exploring the Relationship between Idiomatic Expression Mastery and Reading Comprehension among Students - Melina Ayu Pratiwi; Istiqomah Nur Rahmawati; Yulan Puspita Rini (Jurnal Kajian Penelitian Pendidikan dan Kebudayaan, 2024)
. This research investigates the correlation between mastery of idiomatic expressions and reading comprehension among tenth-grade students at one of high schools in Way Pengubuan during the second semester of the 2022/2023 academic year. Mastery of idiomatic expressions, which improves through childhood and adolescence into adulthood, is essential for accurate comprehension. Reading comprehension is the ability to extract specific information from texts. The study involved 138 students, with a sample of 64 selected through cluster random sampling. Data were collected via tests comprising 20 items each for idiomatic expression and reading comprehension, ensuring the validity of the test items. Analysis was conducted using SPSS 25.0. The findings revealed a high correlation between students' idiomatic expression mastery and their reading comprehension, with a correlation coefficient of 0.986, indicating a strong relationship. This suggests that proficiency in understanding idiomatic expressions significantly enhances reading comprehension.